The Canadian Reconciliation Barometer: a rigorous tool for tracking reconciliation in Canada - Starzyk, K. B.; Neufeld, K. H. S.; Efimoff, I. H.; Fontaine, A. S. M.; White, E. E.-L.; Moran, R.; Peachey, D.; Fontaine, L. S.; Welch, M. A. (Frontiers in Social Psychology, 2024)
Indigenous peoples in Canada have resisted centuries of colonial harm. In response to their resurgence and calls for justice, Canada is now on what is likely to be a long and winding truth and reconciliation journey. To help monitor perceptions of reconciliation progress in a good way, our team of Indigenous and non-Indigenous researchers created the Canadian Reconciliation Barometer. In Study 1, we wrote 89 self-report items representing 13 factors of reconciliation, which reflected what we learned from Elders, Survivors, and reconciliation leaders. A national sample of 592 Indigenous and 1,018 non-Indigenous participants completed the initial item pool. Exploratory factor analyses indicated that a 13-factor model had excellent fit, with only two factors needing minor conceptual modifications. We retained 64 internally consistent items representing 13 factors of reconciliation: Good Understanding of the Past and Present, Acknowledgment of Government Harm, Acknowledgment of Residential School Harm, Acknowledgment of Ongoing Harm, Engagement, Mutually Respectful Relationships, Nation-to-Nation Relationships, Personal Equality, Systemic Equality, Representation and Leadership, Indigenous Thriving, Respect for the Natural World, and Apologies. In Study 2, a national sample of 599 Indigenous and 1,016 non-Indigenous participants completed the retained items. The hypothesized factors had excellent fit, and the factor structure did not differ between Indigenous and non-Indigenous participants. We conclude by discussing contributions to social-psychological conceptualizations of reconciliation and how to use the Canadian Reconciliation Barometer to monitor social change.